Internalizing psychological symptoms in children and adolescents with fructose malabsorption - Maurer, Annabel; Lieb, Adrian; Bongard, Stephan (Frontiers in Psychology, 2024)
Due to an inhibited tryptophan resorption, patients with fructose malabsorption are expected to experience decreased serotonin synthesis. A deficiency of serotonin may cause internalizing mental diseases like depression and anxiety, and a fructose-oriented eating behavior may affect these symptoms. The parents of 24 children and adolescents with a currently diagnosed fructose malabsorption aged 4;00-13;02 years (M = 8.10, SD = 2.05), the parents of 12 patients with a currently confirmed combination of fructose and lactose malabsorption aged 4;00-12;11 years (M = 8.07, SD = 2.11) and the parents of a comparative sample of 19 healthy participants aged 5;00 to 17;07 years (M = 9.06, SD = 3.04) were interviewed. The interviews were conducted using a screening questionnaire of the German "Diagnostic System of Mental Disorders in children and adolescents based on the ICD-10 and DSM-5 DISYPS-III" and a selfdeveloped questionnaire on eating, leisure and sleeping behavior. On standardized scales parents of children with fructose malabsorption reported higher levels of Depression compared to symptoms of Attention-Deficit/Hyperactivity Disorders (ADHD) and Oppositional Defiant and Conduct Disorders (ODD/CD). Compared to healthy controls, for patients with fructose malabsorption, higher symptom levels of Depression and Anxiety were reported. With regard to eating behavior, within the group with a combination of fructose and lactose malabsorption, a strong positive association between an increased fruit sugar consumption and higher levels of Anxiety and Obsessive-Compulsive Disorders/Tics were found.These results suggest a close association between fructose malabsorption and elevated internalizing psychological symptoms in children and adolescents.